Laboratory investigation of intra-tooth variability in microbial communities from clinically isolated root canal and filling material - Maxi Müller; Ann-Kathrin Weber; Christian Tennert; Lamprini Karygianni; Annette Wittmer; Kirstin Vach; Fabian Cieplik; Ali Al-Ahmad; Konstantin J. Scholz (Clinical Oral Investigations, 2026)
Abstract Objective Studies on the microbiota of endodontic infections mostly investigate samples from only one, the largest or symptomatic, root canal. This study evaluated the endodontic bacterial composition in multi-rooted teeth by analyzing each root canal (RC) and the root canal filling material (FM) separately, evaluating associations with clinical and radiographic parameters. Methods RC and FM samples were collected from 12 teeth. Percussion tests and preoperative radiographs (assessing FM length, homogeneity, periapical index (PAI)) were performed. Culture techniques including calculation of total bacterial count (TBC) and anaerobic/aerobic bacteria followed by identification using MALDI-TOF and 16S rDNA-PCR were conducted. Data were analyzed using mixed linear models (α = 0.05). Results Bacterial growth was detected in 27/33 RC and 18/26 FM samples (11/12 teeth). 81 species (41 aerobic/facultative anaerobic/fungi, 40 anaerobic) were identified. There were frequent differences in microbial composition and TBC between root canals of the same tooth, though these were not significant (n.s.). Dentiradicibacter hellwigii (gen. nov., sp. nov.) was identified for the first time. In teeth with FM ≥ 3 mm short of the apex and homogenous FM, anaerobic bacteria predominated in RC and FM samples ( p = 0.0412). Positive percussion sensitivity correlated with higher aerobic/facultative anaerobic TBC ( p = 0.002). PAI Scores ≥ 4 showed higher anaerobic TBC ( p = 0.0466). Conclusions Microbial composition varies between individual root canals of a tooth and between root canals and filling materials. The TBC was associated with FM quality and clinical parameters. Clinical relevance Comprehensive assessment of all root canals is necessary to fully capture the microbial community of endodontic infections.